The reality of organizational structures and the possibility network structure (Survey of Asser Government agencies ) - Almahi, Mohamed Alamin Ahmed; Hattan, Mohammed Ibrahim Ali (Journal of Economic, Administrative and Legal Sciences, 2020)
The study aimed to evaluate the status of organizational structures and the applicability of network structure in Asser region. The problem of the study is the weakness and inadequacy of current organizational structures. The importance of the study lies in diagnosing the reality of organizational structure and recognizing the supporting and opposing aspects to the network structure Applicability. To achieve the purpose of the study, the descriptive method, that describes, analyzes and interprets the phenomenon, was used in order to reach meaningful generalizations.The study community consists of all employees of quality units and administrative development in various job names with (45) government departments for (90) employees. A range of statistical methods such as arithmetic mean, Pearson coefficient and standard deviation were used.The study showed a number of results, the most important of which are that: The application of the network structure contributes significantly in improving the quality of services, and the Saudi work environment is very encouraging for the application of network structure. In addition, the organizational structures in Asser region are well suited to support and achieve the strategy to a great extent. The results also showed that the design of the structures using the method of network structure is less than expected (medium). The study made some recommendations, the most important of which: Evaluating the effectiveness of structures periodically, updating job description cards, eliminating the overlapping of responsibilities between units and strengthening the orientation towards network organization with further studies on the subject of network structures.
Keywords: organizational structure; network structure